STRATEGI RUMAH SAKIT UMUM DAERAH (RSUD) MANDAU DALAM PELAYANAN PASIEN TUBERKULOSIS (TB) - Kislewina Winri; Harapan Tua RFS (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Health is the main capital in the conduct of the activity of living a life. However, it cannot be denied that the world is faced with problems of emergency of Tuberculosis. To minimize to eradicate Tuberculosis, then WHO set out a global strategy namely the Directly Observed Treatment Short-course (DOTS) since 1995. The DOTS strategy has five components, among others, the political commitment, case detection through the examination of sputum microscopic, the patient should be accompanied by Swallowing Drugs (PMO), the availability of Anti-Tuberculosis Drugs (OAT), as well as monitoring are also reporting on the results of treatment of patients. The implementation of the DOTS strategy in Mandau Hospitals can not be said to be the maximum, because the area Mandau became one of the largest contributor to the number of Tuberculosis in the area of Riau. Keywords: DOTS Strategy, Tuberculosis.